Is Bangladesh Moving toward Herd Immunity? Current COVID-19 Perspective (Bangladesh Journal of Infectious Diseases, 2020)
Globally, a spectrum of infectious disease outbreaks like SARS in 2013, Ebola in 2014, MERS in 2015, and currently COVID-19, have affected us in the early phase of this century and coerced the people across the world to search the adamant control measures to avert the pandemic by any means. Unfortunately, high economic costs and resource-limitations, especially in low-and middle-income countries, restrict the adoption of the epidemic control measures in most cases. Since late December of 2019, the SARS-CoV-2 virus has been creating a breakneck public health concern worldwide. Currently, there is no effective drug to tackle the COVID-19 infection or vaccine yet to be approved. An old-age concept, herd immunity might be a prospective option in this uncertain situation to fight the COVID-19 pandemic. A minimum fraction of people need to be immunized through vaccination or previous infection to attain the herd immunity base that may build an obstacle to free the community from the disease. The insusceptible or indirectly immunized people can act as an invisible shield to impede the epidemic's dispersion anymore.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S63-S66